A Wireless Sensor Networks-based Intelligent System for Library Air Quality Monitoring - Zhang, Xiaoguang; Zhao, Yijie; Zhao, Wei; Xu, Wei-wei; Ji, Wen-chao (International Journal of Online and Biomedical Engineering (iJOE), 2016)
A system for monitoring library air quality by using the emerging technology of Wireless Sensor Networks (WSN) was proposed. Wireless sensor networks can sense and collect data, as well as carry out a real-time monitoring of various environmental parameters, and send data to the end user. Simulation results prove that the proposed system is a power-saving, low-cost and easy-to-use monitoring system, which is efficient enough to be used as a reliable library air quality (LAQ) monitor.